THE INFLUENCE OF LOAN TO DEPOSIT RATIO, NON-PERFORMING LOAN, CAPITAL ADEQUACY RATIO AND RETURN ON ASSETS OF CREDIT DISTRIBUTION AT COMMERCIAL BANKS IN INDONESIA 2017-2020 - Bella, Bella (jfpublisher, 2022)
The purpose of this study is to partially determine the effects of Loan to Deposit Ratio (LDR), Non-Performing Loan (NPL), Capital Adequacy Ratio (CAR) dan Return on Assets (ROA) Against The Distribution of Credit in Commercial Banks in Indonesia for the Period 2017-2020. This research was conducted on Conventional Commercial Banks registered in the IDX during the period of 2017-2020, i.e., 41 conventional banks. The independent variables in the study are LDR, NPL, CAR and ROA, while the dependent variable is Credit Distribution. The data analysis technique used in this study is pooled data linear regression to get a comprehensive picture of the relationship between one variable and another using Microsoft Excel dan Eviews version 9 to process the research data. From the results of the study it is known that LDR has a significant positive effect on the distribution of credit to commercial banks in Indonesia which means the hypothesis is accepted. NPL has a significant positive effect on lending to commercial banks in Indonesia which means the hypothesis is accepted. CAR is positive value but does not have a significant influence on credit distribution to commercial banks in Indonesia which means the hypothesis is rejected. ROA is negative but does not have a significant influence on credit distribution in commercial banks in Indonesia which means the hypothesis is rejected.